Assessing the impact of COVID-19 pandemic in vulnerable social groups in Athens, Greece. (20th October 2021) - Roussos, S; Anagnostou, O; Detsi, I; Kokolesis, E; Malliori, M; Kalamitsis, G; Sypsa, V; Hatzakis, A
Abstract: Background: The first case of SARS-CoV-2 in Greece was identified in February 2020. During the COVID-19 pandemic two lockdowns took place (March-May 2020/November 2020-ongoing). People who use drugs (PWUD), as well as the homeless, constitute vulnerable social groups. The main aim of this study is to assess the impact of social distancing measures during the COVID-19 pandemic on these groups. Methods: A program was implemented in Athens between December 2020 and January 2021 in a sample of PWUD and homeless recruited both in Substitution Treatment Units and the Homeless Shelters. The interview was conducted with a structured questionnaire. Results: The study included 303 participants (215 PWUD and 88 homeless individuals (HI)). The mean (SD) age was 49.2 (9.7) and 61.9 (10.2) years for PWUD and HI respectively. Chronic hepatitis C was reported by 33% of PWUD and 1.1% of HI. HIV infection was reported in 9.3% of PWUD. Testing for SARS-CoV-2 was reported by 55% and 100% of PWUD and HI respectively; 0.8% of PWUD and 5.7% of HI were found positive. Compliance with individual measures against SARS-CoV-2 was reported to be high (98-100%) during lockdowns. 88.8% and 98.9% of PWUD and HI reported change in the quality life. Feelings of isolation were reported by 46.6% and 11.5% on PWUD and HI, respectively. PWID enrollment in OST programmes during the 1st and 2nd lockdown was 67.1% and 92.9% respectively. OST attendees did not report changes in treatment during lockdowns. Access to hygiene materials was 9.8% and 100% in 1st and 2nd lockdown. Access to drugs was high (91.5% and 94.3%) in both lockdowns. The illegal drug use as compared to regular use was increased 12.2%/14.3%, decreased 40.2%/40%, stable 47.6%/45.7% for 1st/2nd lockdown respectively. Conclusions: The population studied is well-aware and compliant with the prevention measures against COVID-19 with access to frequent laboratory testing, low levels of SARS-CoV-2 and access to prevention materials. Key messages: Among PWUD the OST services provision was stable. Provision of antiseptics was higher during the 2nd lockdown while changes in drug use were similar during the 1st and 2nd lockdown. Limitation: This study does not assess PWUD with limited access to OST and HI living in the streets.